Implementation of Accessibility as a Passive Fire Protection System in the Hutaraja Village Tourism Area in Pangururan District, Samosir Regency - Rahman, Vinky; Abdillah, Wahyu; Pane, Imam Faisal (Talenta Publisher, 2025)
The Simarjarunjung corridor area is one of the tourist destinations in Simalungun Regency, North Sumatra, which is famous for its natural scenery and culinary specialties. With the development of tourism activities, the appearance of buildings along the corridor of this area has changed. This study aims to analyze the typology of building facades in the Simarjarunjung area and its influence on the formation of the character of the area. The method used is a qualitative descriptive method, where data collection is carried out through field observations, documents, and interviews. The research sample focused on buildings along the main corridor of Simarjarunjung. The results of the study show that there are three main types of building facades according to the shape, material, and elements of the facade. The first typography reflects the old architectural style with wood materials and hip roofs. The second type is a modern minimalist building, mainly glass and concrete. The third type is a mixed-style building that combines traditional and modern elements. The diversity of these types creates the unique character of a tourist destination area that combines local cultural elements with modern needs. This study shows the need for design guidelines as guidelines for building facades that can strengthen the identity of the Simarjarunjung area as a tourist destination based on local culture.